2006
DOI: 10.1038/sj.mp.4001882
|View full text |Cite
|
Sign up to set email alerts
|

Association of the κ-opioid system with alcohol dependence

Abstract: Opioid receptors and their endogenous peptide ligands play important roles in the reward and reinforcement of drugs such as heroin, cocaine, and alcohol. The binding of dynorphins to the j-opioid receptor has been shown to produce aversive states, which may prevent the development of reinforcement. We genotyped SNPs throughout OPRK1, encoding the j-opioid receptor, and PDYN, which encodes its ligand prodynorphin, in a group of 1860 European American individuals from 219 multiplex alcohol dependent families. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
2
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 65 publications
7
128
2
8
Order By: Relevance
“…In contrast to the study of OPRD1 by Mayer et al, 40 we did not observe an association between the synonymous variant C921T and OD (though a specific haplotype harboring its C-allele was associated with AD, CD, and especially with OD); instead, a significant association between the nonsynonymous variant G80T (or Cys27Phe) and OD was observed. Moreover, our results are consistent with the findings from a recent study by Xuei et al 48 that OPRK1 variants are associated with risk for AD. They found that five SNP variants in OPRK1 intron 2 were associated with AD.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the study of OPRD1 by Mayer et al, 40 we did not observe an association between the synonymous variant C921T and OD (though a specific haplotype harboring its C-allele was associated with AD, CD, and especially with OD); instead, a significant association between the nonsynonymous variant G80T (or Cys27Phe) and OD was observed. Moreover, our results are consistent with the findings from a recent study by Xuei et al 48 that OPRK1 variants are associated with risk for AD. They found that five SNP variants in OPRK1 intron 2 were associated with AD.…”
Section: Discussionsupporting
confidence: 93%
“…As novelty seeking and reward learning are important risk conferring factors with respect to neuropsychiatric disorders, especially addiction, we focused on two SNPs (rs2235749, rs910080) implicated in substance use disorders (Xuei et al, 2006;Yuferov et al, 2009). All genotypes conformed to Hardy-Weinberg equilibrium.…”
Section: ′Utr Polymorphisms Of the Pdyn Gene Are Associated With Behmentioning
confidence: 99%
“…PDYN SNPs rs2235749 and rs910080 (assay IDs 2507439 and 2507541, respectively) were chosen based on published data that specifically implicated the 3′UTR SNPs in substance dependence (Xuei et al, 2006;Yuferov et al, 2009). Linkage disequilibrium (LD) analysis was also carried out for SNPs in the PDYN gene +/ − 10 kb using the 1000 Genomes data based on racially mixed reference populations and with a minor allele frequency of at least 0.05.…”
Section: Genotypingmentioning
confidence: 99%
“…Recent studies of humans of European-American descent demonstrate that variations in the genes encoding KOR and dynorphin, OPRK1 and PDYN, are associated with alcohol dependence (Xuei et al, 2006;Edenberg et al, 2008;Karpyak et al, 2012). In addition, animal studies using rats show that activation of KORs with a selective KOR agonist reduces voluntary ethanol intake (Lindholm et al, 2001), whereas a selective KOR antagonist increases alcohol self-administration (Mitchell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%